Pairwise Voting to Rank Touristic Destinations Based on Preference Valuation - Francisco E. Cabrera (Sustainability, 2019)
This paper presents a novel approach for ranking tourist destinations based on the eigenvector method for pairwise voting (EMPV). The proposed approach relies solely on pairwise comparisons instead of direct-vote polling. The EMPV method was tested over a real-world case application to rank various tourist destinations in the Costa del Sol region, Spain, and its outcome was compared against a polling approach using a Likert-type scale. Results show that the EMPV and the Likert-based approach provided different rankings of preferred tourist destinations. Furthermore, both the EMPV and the Likert-based approaches shared the same preference patterns per ranking position, thus confirming that the reported predilection of the tourist is independent of the measurement approach. Finally, results show that the ranking produced by the EMPV methodology was highly related to the real number of visitors of the Costa del Sol tourist destinations, surpassing the Likert-based approach in both ordering and value similarities.